2021
DOI: 10.1039/d1sc04070g
|View full text |Cite
|
Sign up to set email alerts
|

A switchable sensor and scavenger: detection and removal of fluorinated chemical species by a luminescent metal–organic framework

Abstract: Fluorosis has been regarded as a worldwide disease that seriously diminishes the quality of life through skeletal embrittlement and hepatic damage. Effective detection and removal of fluorinated chemical species such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Interestingly, we found that the center pyrazine core twisted into a nonplanar structure, so we can construct two planes, and the twist angle is 21.1° (Figure S5 ). Thus, the pyrazine ring and phenyl arms dihedral angle become 34.8° and 40.9°, respectively, in Tb-TCPP-1 from 20.1° of free H 4 TCPP [ 38 , 50 ] (Figures 3(b) and 3(e) ). On the contrary, so as to match the 12-c Tb 9 cluster in the she net of Tb-TCPP-2, the two N atoms in pyrazine of TCPP 4- are coplanar to other carbon atoms, which are similar with the H 4 TCPB based shp net Y-shp-MOF-5 and the H 4 TCMB based csq net Y-csq-MOF-1.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that the center pyrazine core twisted into a nonplanar structure, so we can construct two planes, and the twist angle is 21.1° (Figure S5 ). Thus, the pyrazine ring and phenyl arms dihedral angle become 34.8° and 40.9°, respectively, in Tb-TCPP-1 from 20.1° of free H 4 TCPP [ 38 , 50 ] (Figures 3(b) and 3(e) ). On the contrary, so as to match the 12-c Tb 9 cluster in the she net of Tb-TCPP-2, the two N atoms in pyrazine of TCPP 4- are coplanar to other carbon atoms, which are similar with the H 4 TCPB based shp net Y-shp-MOF-5 and the H 4 TCMB based csq net Y-csq-MOF-1.…”
Section: Resultsmentioning
confidence: 99%
“…41 N-heterocycle pyrazine changes the p-bond structure; thus, TCPP sensitizes Eu 3+ ions for their antenna effect emission. Although there are some reports about TCPP, [43][44][45][46][47] the research is not comprehensive. The properties and applications of TCPP are still required to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…7). 126 The In(tcpp) showed dual functions for sensing and removal of fluorinated chemicals. Specifically, In(tcpp) displayed a turn-on detection of F À within 5 min and showed a limit of detection of 1.3 mg L À1 .…”
Section: àmentioning
confidence: 99%